Climate smart practices for intensive rice based systems in Bangladesh, Cambodia, and Nepal. (Metro Manila, Philippines Asian Development Bank, 2019)
It emphasizes learnings from a technical assistance project that aimed to (i) identify constraints on and support for scaling up water saving mechanized technologies; (ii) demonstrate agricultural practices that can improve crop productivity, resilience, and adaptive capacity; and (iii) develop databases to capture survey, on-station, and participatory trial data. The publication is intended to aid succeeding efforts on bringing science based and participatory solutions that can address the needs of rice-farming communities in the three countries.
Keywords: Agricultural resources -- Management; Agriculture -- Economic aspects -- Asia; Electronic books